Septic shock: perspective methods of diagnostics and therapy based on immunopathogenesis - L. I. Gomanova (Медицинская иммунология, 2020)
Based on the III International Consensus on the definition of Sepsis and Septic Shock (Sepsis-3), the modern definition of septic shock was proposed: “Septic shock is a type of sepsis that is accompanied by severe hemodynamic, metabolic and cellular disorders, and these disorders are associated with a higher risk fatal outcome”. Despite the classic idea of septic shock development (proinflammatory, immunosuppressive phases and, finally, multiple organ failure with distinct shock organs), the theory of activation of the caspase, endocannabioid system and system of protein of programmed death-1 in evolving septic shock are promising approaches to development of new diagnostic and therapeutic methods. Lymphopenia is already observed at an early stage of septic shock, which further leads to deep immunosuppression. Previous experimental studies have revealed some treatment methods to reduce the pro-inflammatory stage, which, however, did not show desired results in clinics. Now it is necessary to look for ways to inhibit apoptosis, depletion of lymphocytes, macrophages and other immune cells in the course of septic shock. It is known that caspases mediate innate detection of pathogenic microorganisms, cause pyroptosis, activation of monocytes. It has been proven that inhibition of caspase-8, caspase-11 leads to decreased monocyte functioning and cytokine release, which plays an important role in immunopathogenesis of septic shock. Associations of PD-1 and PD-2 expression on CD4+  lymphocytes and monocytes are also shown to be connected with immune dysfunctions, decrease in lymphocyte proliferation, and increased interleukin-10 concentration. Stimulation of the cannabinoid receptors is able to reduce inflammation by inhibiting cytopathic and immunosuppressive effects of pathogens. It has been shown that classic septic shock biomarkers (pro-inflammatory, anti-inflammatory cytokines; procalcitonin, lactate, etc.) do not have predictive power in relation to the outcome of the disease. Circulating and citrullated histones, determined by mass spectrometry, may serve as potential diagnostic markers of septic shock, but they require further study. Use of oxidized phospholipid oxPAPC (Oxidized 1-palmitoyl-2-arachidonoyl-snglycero-3-phosphocholine), hydrogen sulfide and Fasciola hepatica fatty acid binding proteins (hepatic fluke) prevents oxidative stress, synthesis of pro-inflammatory cytokines and provides maturation of macrophages and dendritic cells. Further study of immunological reactions during septic shock is of great importance for substantiation of new approaches to the diagnostics and therapy of septic shock.